Perancangan Pembangkit Listrik Tenaga Bayu (PLTB) 10 MW di Pulau Sumba, NTT - Harry Setyo Wibowo; Aditya Muhammad Nur; Mukhlis Ali; Dimas Alfredo (Jurnal Teknologi Bahan dan Barang Teknik, 2020)
Wind energy is a renewable energy sources which has big potency to develop in Eastern Indonesia especially in East Nusa Tenggara that has low electrification ratio (58.64%) and mostly depend on Diesel Powered Electric Generator as main electric power generation. One effort to meet electricity needs in NTT is through the development of Wind Powered Electric Generator. One of the islands that have the best wind energy potential in NTT is Sumba Island. Based on consideration of the potential of wind energy, location topography, and transportation access, the most appropriate location for the design of Wind Powered Electric Generator in Sumba Island is the Mondu District. Based on the electricity needs in the island of Sumba of 10 MW, the design of the Wind Powered Electric Generator which is carried out with the concept of a wind farm produces its design with 105 wind turbines with three propellers, each with a power of 100 kW. The total electrical power generated by the PLTB which was designed was 10.24 MW after taking the wake effect into consideration due to the laying of the wind turbine.Energi angin merupakan salah satu energi terbarukan yang potensial dikembangkan di Indonesia Timur terutama di provinsi Nusa Tenggara Timur (NTT) yang masih mempunyai rasio elektrifikasi rendah (58,64%) dan masih mengandalkan PLTD sebagai pembangkit listrik utama. Salah satu upaya untuk mencukupi kebutuhan listrik di NTT adalah melalui pengembangan PLTB. Salah satu pulau yang mempunyai potensi energi angin paling baik di NTT adalah Pulau Sumba. Berdasarkan pertimbangan potensi energi angin, topografi lokasi, dan akses transportasi, lokasi yang paling tepat untuk perancangan PLTB di Pulau Sumba adalah di Distrik Mondu. Berdasarkan kebutuhan listrik di Pulau Sumba sebesar 10 MW, maka perancangan PLTB yang dilakukan dengan konsep ladang angin (wind farm) menghasilkan rancangan PLTB dengan 105 buah turbin angin dengan tiga baling-baling yang masing-masing berdaya 100 kW. Total daya listrik yang dihasilkan oleh PLTB yang dirancang adalah 10,24 MW setelah memperhitungkan adanya wake effect akibat peletakan turbin angin.